The theoretical optical gain of Ge1−xSnx nanowires - Xiong, Wen (2020)
The electronic structures of Ge1−xSnx nanowires at the direct Γ‐valley and indirect L‐valley is calculated using k·p effective‐mass theory, and the results demonstrate that Ge1−xSnx nanowires with large diameter and Sn content can easily be engineered to be the direct‐band‐gap semiconductor. Furthermore, the optical gain of Ge1−xSnx nanowires as functions of the injected electron concentration and diameter are obtained. Compared with pure Ge nanowires, a remarkable peak gain can appear in Ge1−xSnx nanowires even though the injected electron concentration decreases. This is because incorporating Sn into Ge can reduce even reverse the energy difference of minimum bandgap between the direct Γ‐valley and indirect L‐valley. Therefore, considering the free‐carrier absorption loss, one can achieve a positive net peak gain in Ge1−xSnx nanowires, which indicates that Ge1−xSnx nanowires can be used as an ideal laser diode candidate in the field of Si‐photonics.